Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy and intraoperative radiation therapy in the management of gallbladder cancer: a case report - Alaswad, Marwan; Otry, Abdullah Al; Alhosainy, Ziad; Elkordy, Fadwa; Sabbah, Belal Nedal; Arabi, Tarek Ziad; Abdulkader, Humzah; Ghanayem, Obaida Fadi; Azzam, Ayman Zaki; Amin, Tarek (Frontiers in Oncology, 2024)
Gallbladder cancer (GBC) is a rare and highly aggressive malignancy, often characterized by nonspecific clinical presentations and late diagnosis, which contribute to its poor prognosis. It is commonly detected at advanced stages, leading to low survival rates. Surgical resection is the primary treatment, with the extent of surgery depending on the T stage of the cancer. In advanced cases, surgery is only considered if it can potentially be curative. Despite various treatment approaches for advanced GBC, survival outcomes remain poor. In our case series, we introduce a novel treatment approach combining cytoreductive surgery, intraoperative radiation therapy, and hyperthermic intraperitoneal chemotherapy. Remarkably, we observed a 100% one-year survival rate, with one patient achieving eight years of disease-free survival without recurrence or metastasis. This aggressive treatment strategy did not lead to increased morbidity or mortality, suggesting its safety and feasibility. However, larger-scale studies are required to draw definitive conclusions.